دور نظام المعلومات الشامل قي تسيير الموارد البشرية - - شرقي ابراهيم -جديلي لخضر (My University, 2024)
Abstract This study aims to analyze the role of the comprehensive and integrated information system in implementing promotion processes, both for employees holding senior positions and those promoted through promotion schedules. The study was conducted in the municipality of Oultem-M'Sila province, and it involved tracking the various stages of promotion implementation using the comprehensive and integrated information system. The study concluded that the comprehensive and integrated information system assists inimplementingallpromotionprocesses.Ithelps,ononehand,byrememberingthepromotion datesforseniorpositionholdersandprovidingthedecisiontemplate,andonthe otherhand,by highlighting those eligible for promotion through the activation of the promotion icon and automatically ranking the candidates. This significantly saves time and effort for human resources managers.
Keywords: Key Words: Comprehensive and integrated information system; Human resources management; Grade promotion; Promotion schedules.